Patterns of bronchodilator therapy in asthmatic outpatients - Toetik Aryani, - (PagePress Publications, 2023)
Background: Bronchodilators are used to treat asthma symptoms. The administration of this therapy can be given through monotherapy or in combination to achieve the maximum therapeutic effect.